PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENCEGAHAN DAN PENANGGULANGAN PELECEHAN SEKSUAL SISWA DI SMAN 11 PANDEGLANG - Julia, Neng; Mutaqin, Mumu Zainal; Inayatullah, Deden (JURNAL KAJIAN ISLAM MODERN, 2024)
Islamic religious education teachers have a key role in guiding students, providing an understanding of religious values and ethics that can protect them from sexual harassment. Teachers also play a role as mediators in handling cases of sexual harassment that occur in the school environment. However, there are challenges in the implementation of these roles that need to be overcome, such as a lack of adequate training and support. The implication of this study is the need to increase the role of Islamic religious education teachers, more comprehensive training, and cooperation between teachers, students, parents, and schools in efforts to prevent and overcome student sexual harassment.